Video model on social media use skills for adolescents with intellectual disabilities. - Peng, Peng; Fu, Wangqian; Wei, Shouhong (International Journal of Developmental Disabilities, 2026)
Objectives: The purpose of this study was to evaluate the effects of video modeling on the acquisition, maintenance, and engagement of social media use skill of WeChat. Methods: A multi-probe cross-behavior single subject design of intervention was adopted in the study. Video modeling (VM) training was conducted in the treatment room of the special education school in China. Two Chinese adolescents (15-17 years old) with intellectual disability (ID) participated in this study. Results: We found the training was effective in improving social media use skill of WeChat for adolescents with ID by VM, and they acquired a relatively high level of social media use skill of WeChat after the training. And the operation steps of social media use skill influence the learning outcome. Conclusions: VM is a promising intervention approach in the social media use skill learning for adolescents with ID. Parents and educators should take the operation steps of social media use skill into consideration in the VM training.